BIOM-56. THE INTEGRATION OF A LIQUID BIOPSY PROGRAM INTO THE CARE OF PEDIATRIC BRAIN TUMOR PATIENTS. (9th November 2020) - Miller, Alexandra; Szalontay, Luca; Ahmad, Hamza; Bouvier, Nancy; Rodriguez-Sanchez, Irene; Bale, Tejus; Benayed, Ryma; Arcila, Maria; Donzelli, Maria; Dunkel, Ira; Gilheeney, Stephen; Khakoo, Yasmin; et al.
Abstract: Pediatric CNS tumors remain the leading cause of cancer-related death in children and adolescents. Safe sampling of tumor tissue for diagnostic purposes may be difficult if not impossible. Detection of minimal residual or recurrent disease prior to definitive clinical or radiographic progression may allow earlier initiation of novel therapies and ultimately improve overall survival. Given the rarity of serial sampling of tumor tissue, our understanding of molecular evolution in response to therapy remains limited. Recent technological advances have led to the development of "liquid biopsy" assays, which detect cell-free DNA (cfDNA) in blood, cerebrospinal fluid (CSF) or other bodily fluids. Here, we report our initial clinical experience with the recently established MSK Kids pediatric neuro-oncology liquid-biopsy program at Memorial Sloan Kettering Cancer Center (MSKCC) using MSK-IMPACT, which is clinically validated by the New York State Department of Health for CSF cell-free DNA (cfDNA)vprofiling. All CSF samples were collected as part of clinical care, and results reported to both clinicians and patients/families. Samples from 29 unique patients were sequenced. Histopathology included high-grade glioma (5); low-grade glioma (2); medulloblastoma (8); pineoblastoma (3); retinoblastoma (4); other (7). CSF cfDNA could be detected in 18/42 samples (43%) and 12/29 patients (34%). CSF cfDNA was more commonly detected in higher-grade, disseminated tumors such as high-grade glioma (60%), medulloblastoma (38%), and pineoblastoma (100%). Low-grade lesions without leptomeningeal involvement did not result in detectable CSF cfDNA shedding (86% were negative). In a subset of patients, MSK-IMPACT identified previously unrecognized molecular actionable targets (e.g. BRAF-KIAA1549 fusion); or the detection of "minimal residual disease" prior to the detection of tumor recurrence by conventional diagnostics, impacting clinical care decisions. Future directions include integration of CSF cfDNA into prospective clinical trials as a correlative biomarker.